Stage Specific Transcriptomic Analysis and Database for Zebrafish Oogenesis - Bogoch, Yoel; Jamieson-Lucy, Allison; Vejnar, Charles E.; Levy, Karine; Giraldez, Antonio J.; Mullins, Mary C.; Elkouby, Yaniv M. (Frontiers in Cell and Developmental Biology, 2022)
Oogenesis produces functional eggs and is essential for fertility, embryonic development, and reproduction. The zebrafish ovary is an excellent model to study oogenesis, and recent studies have identified multiple regulators in oocyte development through forward genetic screens, and reverse genetics by CRISPR mutagenesis. However, many developmental steps in oogenesis, in zebrafish and other species, remain poorly understood, and their underlying mechanisms are unknown. Here, we take a genomic approach to systematically uncover biological activities throughout oogenesis. We performed transcriptomic analysis on five stages of oogenesis, from the onset of oocyte differentiation through stages preceding oocyte maturation. These transcriptomes revealed thousands of differentially expressed genes throughout oogenesis. We analyzed trends of gene expression dynamics along oogenesis, and their expression in pair-wise comparisons between stages. We determined functionally enriched terms, identifying uniquely characteristic biological activities in each stage. These identified two prominent developmental phases in oocyte differentiation and traced the accumulation of maternally deposited embryonic regulator transcripts in the developing oocyte. Our analysis provides the first molecular description for oogenesis in zebrafish, which we deposit online as a resource for the community. Further, the presence of multiple gene paralogs in zebrafish, and the exclusive curation by many bioinformatic tools of the single paralogs present in humans, challenge zebrafish genomic analyses. We offer an approach for converting zebrafish gene name nomenclature to the human nomenclature for genomic analyses generally in zebrafish. Our work provides a valuable resource as a first step to uncover oogenesis mechanisms and track transcripts of maternal regulators of embryogenesis.